Cytotoxic Effects of Polyhexanide on Cellular Repopulation and Calcification of Decellularized Equine Carotids in vitro and in vivo. Issue 3 (March 2013) - Böer, Ulrike; Spengler, Claas; Klingenberg, Melanie; Jonigk, Danny; Harder, Michael; Kreipe, Hans-Heinrich; Haverich, Axel; Wilhelmi, Mathias
Purpose: Disinfection of biological implants is indispensable for clinical safety. Here, decellularized equine carotid arteries (dECAs) were disinfected by polyhexanide (PHX), an effective, well-tolerated and nontoxic wound disinfectant and evaluated as vascular grafts for their repopulation and local biocompatibility in vivo. Methods: dECAs were terminally disinfected by a combination of 0.1% PHX and 70% ethanol (dECA_PHX-ET) or exclusively ethanol (dECA-ET) and subsequently implanted as arteriovenous shunts in sheep for 14 weeks. Repopulation was determined by immunohistochemistry for endothelial- (ECs) or smooth muscle cells (SMCs) using antibodies against CD31 and smooth muscle actin. Histological evaluation was performed on HE-stained sections. Cytotoxicity of dECAs was measured directly by seeding the scaffolds with L-929 fibroblasts, which were visualized by calcein staining. Indirect cytotoxicity was determined by WST-8 viability assay by incubation of L-929 with dECA extracts. Results: dECA_PHX-ET completely lacked repopulation with ECs and SMCs, showed leukocyte infiltration, strong calcification and poor neovascularization indicating insufficient biocompatibility and inflammatory graft degeneration. PHX-treatment reduced cell viability to 33.2 ± 12.6% and disturbed cell growth at direct contact. In contrast, dECA_ET had no direct cytotoxic effect and only slightly influenced cell viability (82.9 ± 12.5%), showed a substantial repopulation by ECs and SMCs including neovascularization, and were only slightly calcified. Conclusion: The disinfectant polyhexanide seems to exert severe cytotoxic effects when used for the processing of decellularized matrices and may result in degenerative graft deterioration. In contrast, dECAs exclusively disinfected with ethanol were well integrated. Thus, ethanol seems to be a more suitable tool for graft processing than polyhexanide.